PENGGUNAAN SOFTWARE ANATES DALAM PEMBELAJARAN EVALUASI PENDIDIKAN PADA MAHASISWA NON MATEMATIKA FTIK IAIN LANGSA - Nazliati, Nazliati (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2018)
Evaluation is a process of measurement and assessment. It is a very crucial in teaching learning process. Education and teacher training faculty (FTIK) of IAIN Langsa stated that educational evaluation as a compulsory subject that the students have to study. However, some of non-mathematics students face difficulty in analyzing data because of number, formulas and accuracy in calculation. The objective of this study is to determine the use of Anates software in studying educational evaluation. This study is conducted in quantitative method while pretest-posttest group experimental design is used. The unit 3 of PAI students is assigned as a sample by using purposive sampling. The result shown that there is a significant different result between before and after Anates software taught where 3 categories of enhancement have indicated, 47,06% for high level, 35,29% for moderate level and 17,65% for low level. Hence, the use of Anates software can help non mathematics students in studying educational evaluation and the learning process is more efficient and accurate.